Are bygones not bygones? Modeling price level targeting with an escape clause and lessons from the gold standard - Paul R. Masson; Malik D. Shukayev (Bank of Canada, 2008)
Like the gold standard, price level targeting (PT) involves not letting past deviations of inflation be bygones; both regimes return the price level (or price of gold) to its target. The experience of suspension of the gold standard in World War I, resumption in the 1920s (for some countries at a different parity), and final abandonment is reviewed. It suggests that PT would likely operate with an escape clause that allowed rebasing of the price target in the face of large output declines. Using a calibrated general equilibrium model, we show that such an escape clause can produce multiple equilibria. For some parameterizations, there is a low credibility equilibrium (with high expectation of a reset) associated with high output volatility and frequent resets. These problems reduce the expectational advantage of PT over inflation targeting.
Keywords: E31; E52; 330; Credibility; Monetary policy framework; Geldpolitik; Preisniveau; Goldwährung; Gesamtwirtschaftliche Produktion; Volatilität; Theorie